Knotting task execution based a hand-rope relation. (3rd June 2017) - Vinh, Trinh Van; Tomizawa, Tetsuo; Kudoh, Shunsuke; Suehiro, Takashi
Abstract: In this paper, we focus on relationship between the rope and fingers to implement a knot and estimate error occurred during execution of knotting task. In the previous work, the authors have proposed a method for making various knots from synthesis of basic operations called skills that are derived from analyzing the knotting processes. Each individual skill has an operation to handle the rope and conditions for executing and completing the task skill. By combining these skills, we can make the whole knotting process robust. In this paper, the 'relations', which describe the positions of the rope relative to the fingers, found from the successful cases, using the teaching data, were defined as the conditions of the task skills. Relation of rope and fingers at a specific state is presented by using propositional variables and logical connectives. Knotting skills were constructed to be executed robustly using the detected conditions. Occurrence of an error is estimated by finding out an abnormal relation. In this case, a corrective action can be inserted to modify the position of contact points, which are relative to the unsatisfied conditions to satisfy the detected conditions; therefore, skill execution is more reliable. We confirm the effectiveness of the methods through experiments. Graphical Abstract: